Peningkatan Kualitas Knalpot Pada Pt Fajar Indah Menggunakan Metode Six Sigma - Dharmawan, Lauretius Danny; Ekawati, Yurida (Jurnal Teknik Industri, 2014)
PT Fajar Indah is an automotive company which is one of their flagship products is muffler for Colt Diesel FE 120 PS. During 2012 and 2013, PT Fajar Indah was able to produced muffler up to 2400 unit with 6-7% defects rate. There are five type of defects that affects muffler’s quality which are lid’s defects, ring’s defects, defects of resonator’s size, defects of plate’s cutting size, and defects of broken plate. To determine whether improvements are needed in muffler’s prodution process and how they will be conducted so six sigma will be used for analysis. Analysis was conducted using DMAIC process, where recommended action for quality improvement were determined with RCA and FMEA. Result from analysis shows that PT Fajar Indah had 12,879 DPMO value and 3.73 sigma which mean that improvement is needed in muffler’s production process. Some recommended actions that can be done are maintenance scheduling, making work instruction and supervise it, improving storage method for ring’s model, provide place for plate scraps from cutting process, adding more workesr for products inspection, and looking for suppliers who are able to provide plate with standard quality.